Current management and controversies in acute cholecystitis: a narrative review of surgical and nonsurgical strategies, with emphasis on suspicion or incidental detection of gallbladder carcinoma - Lopez, Jorge Eduardo Maldonado; Miranda, Gustavo Rodrigo Limachi; Silva, Salvador Omar Ortiz; Rojas, Yilber Andrés Motta; Orozco, Gabriela Gomez; Barrera, Joshua Matheus Vivero; Briones, Luis Cail Veliz; Román, Oziel Abner de la Cruz (International Journal of Research in Medical Sciences, 2025)
Acute cholecystitis (AC) is a frequent surgical emergency. Laparoscopic cholecystectomy (LC) remains the standard treatment, though debate continues over surgical timing, the role of percutaneous cholecystostomy (PC), and the management of incidental gallbladder carcinoma (GBC). This review analyzed data from randomized trials, meta-analyses, and large observational studies (1966–2023) on these key issues. Evidence supports early LC (within 24–72 hours) as the optimal approach, consistently reducing hospital stay by about 3–4 days (weighted mean difference: –3.07 to –4.1 days, p<0.00001) without increasing mortality or bile duct injury. Operative time is slightly longer (+9.29 minutes, NS). In high-risk patients (APACHE II ≥7), the CHOCOLATE trial demonstrated LC superiority over PC, with lower complication rates (12% versus 65%, p<0.001), fewer reinterventions, and shorter length of stay (5 vs. 9 days, p<0.001). A meta-analysis of 32 studies found PC followed by delayed LC reduced overall complications (RR 0.28, 95% CI 0.14–0.56) but increased biliary leakage when drainage was delayed. Large databases confirm PC alone yields higher mortality and longer hospitalization than LC. Incidentally detected GBC occurs in 0.25–0.89% of cholecystectomies. Registry data show re-resection significantly improves survival for pT2 (44.1 versus 12.4 months) and pT3 (23.0 versus 9.7 months) disease. Early LC is therefore preferred for most AC patients, while PC serves only as a bridge in unstable cases. For incidental GBC, timely re-resection remains essential for curative outcomes, though standardized timing and patient selection criteria require refinement.